Challenges in population monitoring : Bar-tailed Godwits (Limosa lapponica) on the East Atlantic Flyway defy assumed population structure - Conklin, Jesse R.; Bom, Roeland A.; Lindström, Åke ; 0000-0002-5597-6209; Bocher, Pierrick; Piersma, Theunis (Ibis, 2025)
Estimating and monitoring migratory bird populations involves significant challenges, even in the most well-studied and easily-counted species, and can be further complicated by long-held but unverified assumptions and by shifting distributions in changing flyway conditions. We illustrate these challenges using Bar-tailed Godwits Limosa lapponica on the East Atlantic Flyway. The subspecies L. l. lapponica and taymyrensis are considered full leap-frog migrants along this flyway, and all population estimates and status assessments since the 1970s have been based on this premise. However, recent population genetics work has revealed that Bar-tailed Godwits wintering in Europe, previously thought to be 100% lapponica, contain significant numbers—possibly a majority—of taymyrensis. In addition, satellite-tracking of godwits is accumulating evidence for adult taymyrensis individuals that do not migrate to West Africa as expected. Consequently, the actual population size of lapponica is probably only a fraction of the currently accepted estimate of 150 000–180 000 individuals, giving greater credibility to breeding-range estimates (consistently < 30 000 individuals) that historically had been discounted in favour of winter census data. Accordingly, the population size of taymyrensis has probably been greatly underestimated, and the trends in both subspecies should be revisited, as the perceived increasing size of lapponica and decline of taymyrensis may be further confounded by an actual northward redistribution from African to European non-breeding grounds. To more accurately evaluate the population sizes and geographical distribution of the two subspecies on the East Atlantic Flyway, we recommend continued and expanded tracking efforts combined with a large-scale genetic assignment of non-breeding individuals. This case study demonstrates that accurately monitoring of migratory populations requires comparative and multi-disciplinary approaches, and that underlying assumptions should be periodically revisited, particularly in light of rapid environmental change.
Publisher Copyright: © 2025 The Author(s). IBIS published by John Wiley & Sons Ltd on behalf of British Ornithologists' Union.
Keywords: differential migration; individual tracking; migratory flyway; population genetics; population monitoring; status assessment; waders